Análise do discurso de adultos diagonosticados como gagos em três cidades do interior do estado de Pernambuco - Cavalcanti, Tatiana Maria Corrêa (2011)
Most studies on stuttering characterized by decontextualized approaches to the problem that circumscribes from its outward manifestations, which is observable immediately - the symptom. The literature speech heterogeneity of hypotheses about their origin, as opposed to homogeneity in its characterization. However, these approaches converge on one point: stuttering is taken as a manifestation of something that is to be seen in the body, understood as muscle tension, respiration, articulatory production. This study proposes to conduct a discursive analysis of adults diagnosed as stutterers in three cities in the interior of Pernambuco (Macaparana, São Vicente Ferrér e Limoeiro) and analyze what they say about their difficulties in developing their process of language and interaction, immersed in a Table of stuttering. Also tried to identify the brands and discursive properties that characterize the speech of adults diagnosed as stuttering and describe the discursive strategies that serve as supporting the achievement of a possible interaction of creep and vehicle used by the subjects under study. Given the discussions about stuttering speech therapy try to study it, from the linguistic and discursive operation. For this, we endorse in the theoretical assumptions of discourse analysis of the French line (AD) that allowed us a vision of ideological discourse, through theoretical constructs of Marxism, linguistics and psychoanalysis. The AD accesses a linguistics played by ideology, which enables us to raise the notion of normal and pathological crossing the constitution of the subject stuttered speech and speech therapy in addition to sharing a psychoanalytic view of the subject, which is considered important, since there is interest by studying the constitution of the subject-stutterer. To carry out the research used a semi-structured interview with 13 subjects with complaints of stuttering. Our analysis was based on interdiscursivity, where we could identify them as discursive materialized in the speech of individuals. Therefore, we affirm the stuttering as a disorder of language that has a direct relation to production conditions, with a direct order from the speaking subject, the speaker and the situations of stuttering